Reactivity descriptors for MNx non-precious metal complexes as molecular catalysts for electrochemical reactions - Zagal - Moya; José (2023)
1 FINAL REPORT Project 1181037 March 30,2022 This report is structured as a description of the activities performed, including publications and their relationship with the objectives of the proposal. A general objective of this project was to develop a rational method to "tune" the redox properties and adsorption energies of intermediates of a reaction catalyzed by molecular catalysts MN4 ("binding energy from reactant to active center") to obtain a maximum electrocatalytic activity for a given electrochemical reaction. This goal was fully achieved, especially for the oxygen reduction reaction (ORR) where we generated 30 publications (29 WOS publications and one book chapter) during the 4 years of the project, see publications: [1,2,4,5,6,7,8,9,10,11,14,15,16,17,21,22,23, 24,25,26,28,29 ] included in this report, cysteine [16] and thioglycolic acid oxidation [2] and hydrazine [26] oxidation. The most important finding about these reactivity descriptors is that they are apparently are valid for any electrochemical reaction and are therefore universal so the achieved goals of this proposal have a larger impact in electrochemistry as established general reactivity guidelines for designing electrocatalysts for many reactions with applications not only in energy conversion devices [4,6,10,12,27,28], and electrolyzers but also in the design for low cost materials for electrochemical sensors [17]. The most important reactivity descriptors for the oxygen reduction reaction (OER) are the M-O2 binding energy and the M(III)/(II) redox potential of the MN4 catalyst [1,2,3,4,5,7,8,9,11,14,15,,16,22,23,,24,25,28,29]. These eacii decio can be ailoed b chooing he cenal meal M b changing he elecon- withdrawing or electron-donating character of the ligand (2) and by using an axial ligand with certain electron- withdrawing or electron donating character. Figure 1(a) illustrates the effect of the nature of the metal and the effect of changing the ligand. For example, for Co complexes different ...